1991
DOI: 10.1111/j.1744-7348.1991.tb05348.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of prunus necrotic ringspot virus using plum pollen and thrips

Abstract: Prunus necrotic ringspot virus (PNRSV) was transmitted to cucumber but not to peach seedlings after they were dusted with infective plum pollen and caged with 8 -10 thrips per seedling for 24 h. When the pollen was taken from three plum trees shown by mechanical inoculation tests to have highly infective flower buds and pollen, the transmission rates to cucumber seedlings were 56% with Thrips tabaci and 66% with a mixture of five thrips species collected from Ageratum houstonianurn flowers. However, the transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 6 publications
1
23
0
1
Order By: Relevance
“…Both viruses are spread rapidly to neighboring plants (Greber et al 1991;Uyemoto et al 1992;Herrera et al 1998). Field monitoring has shown that in peach orchards in the area of Naoussa (northern Greece), nearly all trees were PPVinfected, while a significant percentage of them were also PNRSV-infected (48%) (Varveri and Bem 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Both viruses are spread rapidly to neighboring plants (Greber et al 1991;Uyemoto et al 1992;Herrera et al 1998). Field monitoring has shown that in peach orchards in the area of Naoussa (northern Greece), nearly all trees were PPVinfected, while a significant percentage of them were also PNRSV-infected (48%) (Varveri and Bem 1995).…”
Section: Introductionmentioning
confidence: 98%
“…However, feeding punctures and faeces could be observed on the PSTVd-infected leaves after the release of T. tabaci and F. occidentalis. Giving the thrips access to feed on pollen and/or PSTVd-infected or non-infected plant material did not contribute to viroid transmission as recorded for transmission of pollen-associated ilarvirus by T. tabaci (Sdoodee and Teakle 1987;Greber et al 1991).…”
mentioning
confidence: 81%
“…Till now no investigations of the possible role of thrips and Apis mellifera as vectors for PSTVd or other pospiviroids have been published. Thrips are well-known virus vectors, especially for tospoviruses (German et al 1992) and ilarviruses Teakle 1987, 1993;Greber et al 1991). The polyphagous species (Lewis 1997) Thrips tabaci and Frankliniella occidentalis are of particular interest in a European context.…”
mentioning
confidence: 99%
“…Thrips were used to test the transmission of PNRSV to cucumber and peach seedlings using thrips as vector by applying the infected plum pollen onto cucumber and peach seedlings (Greber et al, 1991. It was found that Fifty six percent of virus was transmissible on to both seedlings with Thrips tabaci and sixty six percent with a mixture of five thrips species when pollen were taken from highly infected flower buds whereas only 7 percent transmission rate was reported when pollen was taken from flowers with less infectivity.…”
Section: Transmission and Host Rangementioning
confidence: 99%